Toward more objectives teaching clinical skills: - Rasul Hatem, Hikmat. A. (Journal of the Faculty of Medicine Baghdad, 2011)
the clinical teaching courses so far did not take the required attention and unfortunately because on granted that all doctors are expert in it without attention on directions ,for that reason we think that all clinical teaching is the most neglected part of medical teaching and for this reason it is found that there are many deficit in it and it is worsening that ward round were haphazard and taking excitement in many aspects.for this reason more than attention is needed to construct more effective clinical courses and teachers have to be trained on it.As it has been noticed that this needs more research and we should check the following :1. Monitoring the active participation by the student and how many of them stand as on observation only.2. Any of problem been solved during the clinical session and dose the clinical exercise contribute to solving of clinical problem.3. Where are most focused been given, is it to basic and clinical science or it has been spend on for other materials.4. Do the student been supervised closely while they interview the patient at bedside.5. Did the student given enough time to practice their skills.6. Does the teaching in the session is patient oriented or disease oriented. if the answer to these above questions were yes then this is typical clinical tutor but many students in the study shows the contrary.we can try to plan the technique which can be introduced to improve our clinical teaching.